1997
DOI: 10.1037/1076-8971.3.2-3.428
|View full text |Cite
|
Sign up to set email alerts
|

Pretrial publicity: The media, the law, and common sense.

Abstract: As media coverage becomes more extensive and accessible, it is likely to become more difficult to find jurors who have not been exposed to relevant pretrial publicity. Courts' assessments of the likelihood that pretrial publicity has resulted in prejudice against a defendant and of jurors' ability to disregard any prejudice are often based on judicial common sense and often reflect a misappraisal or misunderstanding of the capabilities and weaknesses of human inference and decision making. Therefore, social sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 58 publications
2
79
1
3
Order By: Relevance
“…Simpson trial. Studebaker and Penrod (1997;Studebaker et al, 2000) reported that in the original Oklahoma City venue there were 939 articles published in the Daily Oklahoman between April 1995 and January 1996, that105 of them were on the front page, and that the stories were accompanied by 307…”
Section: Sources Of Pre-trial and Mid-trial Prejudice Media Publicitymentioning
confidence: 99%
“…Simpson trial. Studebaker and Penrod (1997;Studebaker et al, 2000) reported that in the original Oklahoma City venue there were 939 articles published in the Daily Oklahoman between April 1995 and January 1996, that105 of them were on the front page, and that the stories were accompanied by 307…”
Section: Sources Of Pre-trial and Mid-trial Prejudice Media Publicitymentioning
confidence: 99%
“…Thus, judges rely (perhaps naively) on jurors' promises of fairness and impartiality despite their pretrial knowledge about the case (Moran and Cutler, 1991), and further presume that jurors will refrain from attending to publicity about the case during the trial. In both the US and England, judges typically rely on their 'common sense' to assess the effects of any potentially prejudicial pretrial knowledge (Studebaker and Penrod, 1997;Corker and Levi, 1996). Only rarely will a judge grant a request for a change of venue to a different location.…”
Section: Publicity and Juriesmentioning
confidence: 99%
“…Some of the more common remedies include changing the trial venue, gagging the press, using voir dire to select jurors with no exposure to PTP or to neutralize its effects, continuance, and judicial admonitions (Kramer et al, 1990;Studebaker & Penrod, 1997). Most of these remedies are either impractical-such as continuance, changing the venue, or selecting jurors with no exposure-or carry other adverse effects, such as restricting media rights.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the effects of negative PTP about both litigants were examined. Based on the robust nature of PTP effects in criminal cases (e.g., Steblay et al, 1999;Studebaker & Penrod, 1997), as well as the effects of inadmissible evidence in civil cases (Landsman & Rakos, 1994;Tanford & Cox, 1988), we hypothesized that exposure to negative PTP about either party would reduce mock jurors' verdicts for that party, relative to a control condition with no prejudicial PTP.…”
Section: Methodsmentioning
confidence: 99%